Penerapan Konvensi ILO Terhadap Anak Yang Bekerja Di Negara Indonesia Dan Negara Singapura - Siti Nurjanah; Leny Pratiwi (Fakultas Hukum, Universitas Internasional Batam, 2015)
Child means a person who has not completed his 18th year of age. Children must be protected especially for violence, discrimination, right for child, child work for life, and family, etc. International Labour Organization (ILO) is a organization to accept issues worker/employment under United Nation (PBB). ILO has made regulation for child worker like ILO Convention Number 138 about Concerning Minimum Age For Admission To Employment and ILO Convention No. 182 Concerning The Prohibition And Immediate Action For The Elimination Of The Worst Forms of Child Labour. Some report about child worker below minimum age, type of work for child labor, and working hours are not allowed to work has happened right now like sell newspaper at night and child working at handphone shop.This research is a normative law by using the method of comparative law . The data used in the form of secondary data . As for the data mining is done with literature (library research) and interviews. After all the data collected, the data will be processed and analyzed, the qualitative analysis is used to mean the group data studied aspects. Furthermore, the conclusions drawn related to this research, then described descriptively .Based on the results of this study, its showed that some application and to hold Convention ILO Number 138 and 182 also conviction to applied has given protection still to increase because so many cases child working and the penalty not give to discourage for people acted against the law.